1980
DOI: 10.1210/jcem-51-5-968
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Defect in Regulation of Prolactin Secretion after Successful Pituitary Tumor Removal in Women with the Galactorrhea-Amenorrhea Syndrome*

Abstract: TRH, metoclopramide (MCP), chlorpromazine (CPZ), and insulin (ITT) stimulation tests of PRL secretion were carried out in age-matched controls and before and after successful removal of pituitary prolactinomas in women with the galactorrhea-amenorrhea syndrome. In preoperative patients there was a blunted or absent PRL response to TRH in 87%, to MCP in 100%, to CPZ in 100%, and to ITT in 93%. Two to 6 months after successful tumor removal, serum PRL rose 2-fold (the usual criterion for a normal response) in 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The normalization of PRL-responses to TRH after successful hypophysectomy confirms the previous reports (Barbarino et al 1979;Tucker et al 1980;Schlechte and Sherman 1981), although these authors could not observe the distinct responses before the surgery.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The normalization of PRL-responses to TRH after successful hypophysectomy confirms the previous reports (Barbarino et al 1979;Tucker et al 1980;Schlechte and Sherman 1981), although these authors could not observe the distinct responses before the surgery.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, if the pituitary tumor was removed completely , the recovery of normal lactotrophs from the tumor compression and of PRL responsiveness to exogenous stimuli would be expected. Although there are several reports regarding the changes of responsiveness after hypophysectomy, the results are not always consistent (Barbarino et al 1979; Murray et al 1979;Tucker et al 1980; Schlechte and Sherman 1981).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The provocative agents included thyrotropin releasing hormone (TRH), chlorpromazine, levodopa, carbidopa, domperidone, nomifensine and insulin induced hypoglycemia [24][25][26][27][28][29][30]. Unfortunately all of these tests are nonspecific and blunted prolactin responses occur in patients with prolactinomas, hypothalamic tumors and in non-tumoral hyperprolactinemia.…”
Section: Dynamic Tests Of Prolactin Secretionmentioning
confidence: 99%
“…Only few studies have been performed along this vein and results sometimes conflicting have been reported 2, 33, 44, 50. In particular, some studies 44,50 have reported in patients after surgery appropriate PRL responses to TRH and metoclopramide and blunting of the PRL response to insulin hypoglycemia and chlorpromazine. Furthermore, according to some authors 5o but not others 4 the PRL responses to TRH and metoclopramide are reduced in the first months after surgery and return to normal later on.…”
Section: Prolactinomasmentioning
confidence: 99%